7y-113=-y-9

Simple and best practice solution for 7y-113=-y-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7y-113=-y-9 equation:


Simplifying
7y + -113 = -1y + -9

Reorder the terms:
-113 + 7y = -1y + -9

Reorder the terms:
-113 + 7y = -9 + -1y

Solving
-113 + 7y = -9 + -1y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add 'y' to each side of the equation.
-113 + 7y + y = -9 + -1y + y

Combine like terms: 7y + y = 8y
-113 + 8y = -9 + -1y + y

Combine like terms: -1y + y = 0
-113 + 8y = -9 + 0
-113 + 8y = -9

Add '113' to each side of the equation.
-113 + 113 + 8y = -9 + 113

Combine like terms: -113 + 113 = 0
0 + 8y = -9 + 113
8y = -9 + 113

Combine like terms: -9 + 113 = 104
8y = 104

Divide each side by '8'.
y = 13

Simplifying
y = 13

See similar equations:

| z^2+2z-7-6i=0 | | k^2-9k+4=0 | | 8v^2-2v-8=0 | | y^2+8y-1=0 | | z^2+2z-13=0 | | 2x+15=2x-x^2 | | (x-100)(200-.5x)=0 | | 2e-16=42 | | 3j^2+8j-4=0 | | 3x+9=4x-1 | | 5d-2=2d+3 | | 4m^2-5m+1=0 | | 5d-2=2d | | 18=2x^2 | | 3x+1=x+19 | | 6s^2-4s-4=0 | | 4(3-x)+9=7(2+x)+29 | | 7p+15-5p+10=-17+13p | | (-9x)+6-3x+(-18)=12 | | 6k^2-4k-9=0 | | 23x+26=49 | | 5g-18+2g+13=g+19 | | 7g^2+2g-3=0 | | 26.722-3.9v=-7.4(1.2+7.4v) | | -2n+22=6-7(n-8) | | 3w^2+7w-2=0 | | 9x-5=301 | | -8(3x+1)=-2x+14 | | 3x+15-6x-10=x+1 | | v^2+14v=41 | | 108r^2-147= | | 4x+(86400-4x)=86400 |

Equations solver categories